Identifying Student Misconceptions on Momentum and Impulse Using Four-Tier Diagnostic Test Instrument with CRI - Paramita, Uci Vebia; Jauhariyah, Mukhayyarotin Niswati Rodliyatul (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Identification of students' misconceptions is crucial in Physics learning as an evaluation tool to address and reduce these misconceptions. This study aims to assess the quality of a four-tier diagnostic test using the CRI instrument, assisted by JotForm, and describe the profile of students' misconceptions related to momentum and impulse. The quality of the instrument is evaluated based with validity and reliability. The research follows the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method. The instrument is developed during the analysis, design, and development stages. The implementation and evaluation stages involve capturing the profile and causes of students' misconceptions. The instrument's quality is assessed based on theoretical validity, which reached 89.29%. Empirical content validity haved percentages of false positives 6.93%and false negatives 6.53%. The empirical validity of the construct, with a significance level of 0.05, resulted in an rtableof 0.273. From the 15 questions tested, 12 questions were found to have empirical validity, and a reliability score of 0.475 was obtained. The study revealed that 3 students had low misconceptions, 14 students had medium misconceptions, and 6 students had high misconceptions. The causes of students' misconceptions were primarily false positives and humanistic thinking, accounting for 28.56%. In conclusion, the instrument developed in this study is valid and reliable, and it effectively identifies the profile and causes of students' misconceptions.